DSRM: An Ontology Driven Domain Scientific Data Retrieval Model - Jianghua Li; Qing Cao (Institute of Advanced Engineering and Science, 2014)
With the development of information technology, a large number of domain scientific data have been accumulated with the characteristics of distribution and heterogeneity. It has important significance to acquire exact scientific data from multiple data sources for cooperative research. The existing data integration and information retrieval techniques cannot solve the problems of data semantic heterogeneity and retrieval inaccuracy very well. In this paper, an ontology driven domain scientific data retrieval model is proposed, which uses domain ontology to describe user query and queried data. User query is posed on domain ontology schema. Data retrieval for distributed and heterogeneous data sources is realized through constructing mapping relations between them and domain ontologyschema. We developed a prototype for material scientific data, and the experimental results show that the proposed model is effective. Our model can also provide some means of use for reference to other domain scientific data retrieval. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3860